2007
DOI: 10.1002/chin.200726013
|View full text |Cite
|
Sign up to set email alerts
|

High‐Pressure Synthesis and Properties of Solid Solutions Between BiMnO3 and BiScO3.

Abstract: 3 . -The solid solutions BiMn 1-x Sc x O 3 (0 ≤ x ≤ 1.0) are synthesized from stoichiometric mixtures of Bi2O3 and Mn2O3 (6 GPa, 1383-1443 K, 60-70 min) and characterized by magnetization, specific heat, and DSC measurements. The structure parameters of BiMn0.9Sc0.1O3 are refined by the Rietveld method from powder XRD data. The compound crystallizes in the monoclinic space group C2/c with Z = 8. The solid solutions exhibit long-range ferromagnetic order for x = 0-0.2. For x ≥ 0.4, the samples show spin-glass-l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…For example, our studies on the BiMn 1-x Sc x O 3 system showed that H c and M r are noticeably increased with increasing x up to x ) 0.2 (and for x ) 0.05: H c ) 80 Oe and M r ) 0.27µ B ), while the saturated magnetization only slightly decreases. 36 In the case of thin-film samples, there exist additional compressive strains in films. In ref 16, it was suggested that the thin-film samples in reality consist of partially oxidized phases because these samples showed much lower ferromagnetic transition temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…For example, our studies on the BiMn 1-x Sc x O 3 system showed that H c and M r are noticeably increased with increasing x up to x ) 0.2 (and for x ) 0.05: H c ) 80 Oe and M r ) 0.27µ B ), while the saturated magnetization only slightly decreases. 36 In the case of thin-film samples, there exist additional compressive strains in films. In ref 16, it was suggested that the thin-film samples in reality consist of partially oxidized phases because these samples showed much lower ferromagnetic transition temperatures.…”
Section: Discussionmentioning
confidence: 99%
“…The exact solutions of the heat-capacity and global spontaneous-magnetization of 2D-Ising model 3 given by Onsager 32 and Yang 33 , respectively, do confirm this classification theoretically. However, it is gradually found that there is diffuse phase-transition without the singularities of the thermodynamic potential in the componentheterogeneous [14][15][16][17]26,27 and finite-size 28,29 systems with time.…”
Section: Discussionmentioning
confidence: 99%
“…Although diffuse phase-transition is common in component-heterogeneous [14][15][16][17]26,27,[45][46][47] and small-size 28,29,48 systems, there is no accurate calculation of the corresponding theoretical models so far 20 . Therefore, the exact results of the all-size order-parameter (Eq.4) in this paper may give some clues to the studies of this kind of phase-transition.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations